Analisis Psikoanalisis Sastra Terhadap Trauma dan Ingatan Kolektif dalam Novel Laut Bercerita Karya Leila S. Chudori - Serli Rosida; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes the representation of psychological trauma and collective memory in the novel Laut Bercerita by Leila S. Chudori through the psychoanalytic approach of Sigmund Freud and Maurice Halbwachs’ theory of collective memory. The research employs a descriptive qualitative method with content analysis techniques applied to the text. The findings reveal that the trauma experienced by the main character, Biru Laut, reflects internal conflicts among the id, ego, and superego, as well as the emergence of various defense mechanisms such as repression, sublimation, and acting out. Trauma is portrayed not only as an individual experience but also as a collective wound affecting families and communities, which manifests in symbolic actions like the Kamisan protest. The novel serves as a cathartic space and cultural archive that voices historical wounds while advocating for justice and social recovery. Thus, Laut Bercerita functions not only as a literary work but also as a reflective medium for understanding and preserving the nation's collective trauma.